2005
DOI: 10.2337/diabetes.54.12.3582
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heterogeneity in Association of the SUMO4 M55V Variant With Susceptibility to Type 1 Diabetes

Abstract: Association studies are a potentially powerful approach to identifying susceptibility variants for common multifactorial diseases such as type 1 diabetes, but the results are not always consistently reproducible. The IDDM5 locus has recently been narrowed to an ϳ200-kb interval on chromosome 6q25 by two independent groups. These studies demonstrated that alleles at markers in the mitogen-activating protein kinase 7 interacting protein 2 (MAP3K7IP2)/ SUMO4 region were associated with susceptibility to type 1 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
3
57
1
Order By: Relevance
“…Some investigators indicate the NF-B pathway is related to the development of type 1 diabetes (19), and other studies (13,20,21) have found a significant association of SUMO4 M55V gene variant with type 1 diabetes in Asian populations. In contrast, several studies have found no such association in European subjects (22,23), and even an opposite association in British individuals was reported (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators indicate the NF-B pathway is related to the development of type 1 diabetes (19), and other studies (13,20,21) have found a significant association of SUMO4 M55V gene variant with type 1 diabetes in Asian populations. In contrast, several studies have found no such association in European subjects (22,23), and even an opposite association in British individuals was reported (14).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these discrepancies could be genetic heterogeneity and gene-environment interaction in different ethic populations. In studies from Asian populations, the frequencies of SUMO4 AA, GA, and GG have been reported to be 49, 41, and 10% in control subjects and 39, 49, and 12%, respectively, in patients with type 1 diabetes (13,20,21). In this study, the frequencies of SUMO4 AA, GA, and GG in our type 2 diabetic patients were 48, 44, and 8%, respectively, similar to the above-mentioned studies in Asia (13,20,21) but different from Caucasian studies (13,22).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the contribution of SUMO4 to susceptibility to type 1 diabetes, we re-sequenced a >2000bp interval of chromosome 6q25, including the whole SUMO4 gene, in a Japanese sample and the identified polymorphisms were subjected to association studies in both Japanese and Korean populations [43]. The M55V variant was significantly associated with type 1 diabetes in the Japanese and Korean populations, and metaanalysis of published studies as well as our own data confirmed a significant association of the M55V variant with type 1 diabetes in Asian (summary odds ratio: 1.29, p = 7.0×10 -6 ), but not Caucasian populations [43], suggesting heterogeneity in the genetic effect of SUMO4 on type 1 diabetes among diverse ethnic groups.…”
Section: Sumo4 On Chromosome 6q25mentioning
confidence: 99%
“…A study by Zou et al showed that SUMO4 Met55Val polymorphism was implicated in some diseases which are closely related to inflammation process [2] . This variant was also revealed to be associated with type 1 diabetes, an autoimmune related disease, in Asian populations [3][4][5] .Recently, the relationship between SUMO4 Met55Val polymorphism and type 2 diabetes has been a subject of interest in the endocrinological community. Studies by Noso [6] and Shimada [7] reported the contribution of the SUMO4 Met55Val polymorphism to type 2 diabetes susceptibility in a Japanese population.…”
mentioning
confidence: 95%